Observation of Arabian and Saharan Dust in Cyprus with a New Generation of the Smart Raman Lidar Polly - Engelmann, Ronny; Ansmann, Albert; Bühl, Johannes; Heese, Birgit; Baars, Holger; Althausen, Dietrich; Marinou, Eleni; Amiridis, Vassilis; Mamouri, Rodanthi-Elisavet; Vrekoussis, Mihalis (My University, 2016)
The atmospheric science community demands for autonomous and quality-assured vertically resolved measurements of aerosol and cloud properties. Aiming this goal, TROPOS developed the fully automated multiwavelength polarization Raman lidar Polly since over 10 years [1, 2]. In cooperation with different partner research institutes the system was improved continuously. Our latest lidar developments include aside the "3+2" measurements also a near-range receiver to measure aerosol extinction and backscatter down to 120 m above the lidar, a water-vapor channel, and measurements of the linear depolarization at two wavelengths. The latest system was built in cooperation with the National Observatory of Athens (NOA). Its first campaign however was performed at the Cyprus Institute of Nicosia from March to April 2015, aiming specifically at the observation of ice nuclei with in-situ and lidar remote sensing techniques in the framework of BACCHUS [3, 4].
Keywords: Atmospheric science; Cyprus